Cross-generational effects of parental low dose BPA exposure on the Gonadotropin-Releasing Hormone3 system and larval behavior in medaka (Oryzias latipes) - Inagaki, T.; Smith, N.L.; Sherva, K.M.; Ramakrishnan, S. (Neurotoxicology (Park Forest South), 2016)
•Developmental BPA exposure in parent altered GnRH3 neural development in offspring.•Locomotor activity of offspring larvae with BPA exposed parents was reduced.•Effects of developmental BPA exposure was cross-generational.•BPA effects in offspring was sensitive to BPA exposure timing and durations of parents. Growing evidence indicates that chronic exposure to Bisphenol A (BPA) may disrupt normal brain function and behavior mediated by gonadotropin-releasing hormone (GnRH) pathways. Previous studies have shown that low dose BPA (200ng/ml) exposure during embryogenesis altered development of extra-hypothalamic GnRH3 systems and non-reproductive locomotor behavior in medaka. Effects of parental low-dose BPA exposure on the development of GnRH3 systems and locomotor behavior of offspring are not well known. This study examines whether the neurophysiological and behavioral effects of BPA in parents (F0 generation) are carried over to their offspring (F1 generation) using stable transgenic medaka embryos/larvae with GnRH3 neurons tagged with green fluorescent protein (GFP). Parental fish were exposed to BPA (200ng/ml) for either life-long or different developmental time windows. Fertilized F1 eggs were collected and raised in egg/fish water with no environmental exposure to BPA. All experiments were performed on F1 embryos/larvae, which were grouped based on the following parental (F0) BPA exposure conditions – (i) Group 1 (G1): through life; (ii) G2: during embryogenesis and early larval development [1–14days post fertilization (dpf)]; (iii) G3: during neurogenesis (1–5dpf); and (iv) G4: during sex differentiation (5–14dpf). Embryos from unexposed vehicle treated parents served as controls (G0). G1 embryos showed significantly reduced survival rates and delayed hatching time compared to other groups, while G4 embryos hatched significantly earlier than all other groups. At 3 dpf, the GnRH3-GFP intensity was increased by 47% in G3 embryos and decreased in G4 embryos by 59% compared to controls. At 4dpf, G1 fish showed 42% increased intensity, while GFP intensity was reduced by 44% in G3 subjects. In addition, the mean brain size of G1, G3 and G4 embryos were smaller than that of control at 4dpf. At 20dpf, all larvae from BPA-treated parents showed significantly decreased total movement (distance covered) compared with controls, with G2 and G3 fish showing reduced velocity of movement. While at 20 dpf no group differences were seen in the soma diameter of GnRH3-GFP neurons, a 34% decrease in SV2 expression, a marker for synaptic transmission, in G1 larvae was observed. These data suggest that parental BPA exposure during critical windows of embryonic development or chronic treatment affects next-generation offspring both in embryonic and larval brain development as well as larval behavior.